Antidepressants and the risk of suicide in young persons – prescription trends and toxicological analyses. (17th June 2013) - Isacsson, G.; Ahlner, J.
<x xml:space="preserve">Abstract</x> Objective To assess trends in the use of antidepressants among young suicides after the warning that these drugs might increase the risk of suicide. Method Individual data of all 845 suicides in the 10‐ to 19‐year age group in Sweden in the time period 1992–2003 (baseline), and in 2004–2010 (after the warning). Outcome data are prescriptions of antidepressants prior to death and detections of antidepressants in post‐mortem toxicology. Results After the warning, suicide in this age group increased for five consecutive years (60.5%). The increase occurred among individuals not treated with antidepressants. Conclusion This study provides further support for the hypothesis that the warning, contrary to its intention, may have increased young suicides by leaving a number of suicidal young persons without treatment with antidepressants.